2018
DOI: 10.1002/jcp.26379
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer diagnosis: Imaging techniques and biochemical markers

Abstract: Breast cancer is a complex disease which is found as the second cause of cancer-associated death among women. Accumulating of evidence indicated that various factors (i.e., gentical and envirmental factors) could be associated with initiation and progression of breast cancer. Diagnosis of breast cancer patients in early stages is one of important aspects of breast cancer treatment. Among of various diagnosis platforms, imaging techniques are main diagnosis approaches which could provide valuable data on patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
259
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 346 publications
(277 citation statements)
references
References 155 publications
(152 reference statements)
1
259
0
3
Order By: Relevance
“…Breast cancer is known as the common cause of cancer‐related mortality and invasive malignancy affecting females worldwide. It was published that the rate of breast cancer incidence and mortality were varied, which might be due to the ethical and geographical reasons . Accordingly, these rates demonstrated at least four‐fold increase in Asian females with highest rates in Americans .…”
Section: Introductionmentioning
confidence: 99%
“…Breast cancer is known as the common cause of cancer‐related mortality and invasive malignancy affecting females worldwide. It was published that the rate of breast cancer incidence and mortality were varied, which might be due to the ethical and geographical reasons . Accordingly, these rates demonstrated at least four‐fold increase in Asian females with highest rates in Americans .…”
Section: Introductionmentioning
confidence: 99%
“…miRNA‐9 is involved in GBM cells' resistance to temozolomide (TMZ) through regulation of drug efflux transporter, P‐glycoprotein. Therefore, delivery of functional anti‐miRNA‐9 reversed the expression of the multidrug transporter, conferred chemosensitivity, and sensitized the GBM cells to TMZ, as confirmed by increased cell death and caspase activity …”
Section: Therapeutic Role Of Exosomes In Cancermentioning
confidence: 92%
“…Cancer is one of the important diseases that are associated with various public health problems in the world . Hence, fast and suitable diagnosis platforms are needed . Several studies reported that a variety of approaches such as cell therapy, immunotherapy, gene therapy, and nanotechnology‐based methods could be applied in the treatment of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of miRNAs is associated with initiation and progression of a wide range of diseases such as diabetes, cardiovascular diseases, cancer, neurodegenerative diseases, infection diseases, and depression . Hence, it seems that these molecules could be introduced as diagnostic, prognostic, and therapeutic biomarkers in different diseases . In this regard, several studies revealed that different miRNAs were related to pancreatic CSCs progression and could be employed as new targets in PC treatment .…”
Section: Pancreatic Cancer (Pc)mentioning
confidence: 99%